Determinant of capital structure across industrial product listed firms: Empirical evidence from Malaysia / Siti Hajar Shuid and Zulaikha Md Hassan - Shuid, Siti Hajar; Md Hassan, Zulaikha (2014)
This research attempt to analyze the determinant of capital structure variable towards the leverage of industrial products sector in Malaysia using the firms listed in main market of Bursa Malaysia (the Malaysian Stock Exchange). This study examines the relationship between leverage (dependent variable) and five determinants identified as liquidity, profitability, growth, firm size and asset tangibility. Industrial products sector in Malaysia producing volume of good such as automobile and parts, chemicals, construction and materials, industrial metals and engineering, mining, electronic & electrical equipment, food production and also including oil and gas producers. The sample data of this study covered the period from 2004 until 2013 based on panel data set comprising 105 firms with total observations of 1050 firm-years. By applying random effects regression model, the result indicates that profitability and liquidity are significant negatively relations to leverage whilst growth, firm size and asset tangibility are positively significant in relations to leverage. Besides, based on the result disclose, the most dominant factor of the capital structure for industrial products sector in Malaysia is profitability. Some prior studies related with theoretical background of determinations of capital structure makes the findings were constant